The Constitutionality of the Presidential Threshold on the 2019 Election in Indonesia: An Analysis on Constitutional Court Decision 72/PUU-XV/2017 - Ridho, M. Zainor Ridho (UIN Sunan Kalijaga, 2020)
Abstract: Article 222 of Law Number 7 of 2017 concerning General Elections requires political parties to obtain a predetermined number of votes threshold to nominate candidates for President and Vice President in the presidential election based on the Panel of Justices of the Constitutional Court’s decision to reject Law of Number 72/ PUU-XV/2017. Law Number 7 of 2017 concerning General Elections has eliminated political parties’ rights to participate in the general elections, especially new political parties participating in the 2019 general election. From a constitutional perspective, the presidential threshold is a constitutional system using the presidential elections because the presidential system is an open legal policy from the legislators. Law Number 7 of 2017 concerning General Elections regulates the political parties participating in the direct president and vice-president candidacy. In legal logic, simultaneous general elections will be flagged with the presidential threshold provisions. The implementation of the presidential threshold rule in the 2019 simultaneous elections is based on the Constitutional Court’s decision not to grant the judicial review of article 9 of Law Number 42 of 2008 related to the presidential threshold, which raises two interpretations. First, the presidential threshold is deemed still needed in the 2019 simultaneous elections. Second, the presidential threshold is deemed no longer relevant to be used in the 2019 simultaneous elections. Then in the Constitutional Court decision No. 53/PUU-XV/2017, the Constitutional Court is adamant that even though the General Election is held simultaneously, the implementation of the presidential threshold is still relevant for use.Abstrak: Norma-norma Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum yang dimohonkan untuk diujikan secara khusus, yakni Pasal 222 tentang persyaratan Perolehan Suara Partai Politik untuk mengajukan Calon Presiden dan Wakil Presiden dalam pemilu, dengan Perkara Nomor 72/PUU-XV/2017 telah ditolak oleh Majelis Hakim Mahkamah Konstitusi. Dalam perspektif konstitusi, menggunakan atau tidak menggunakan presidential threshold sesungguhnya tidak bertentangan dengan konstitusi, karena presidential threshold merupakan kebijakan hukum terbuka dari pembentuk Undang-Undang.Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum telah mengatur hak partai politik peserta pemilu serentak terhadap pencalonan presiden dan wakil presiden secara langsung. Secara logika hukum, pemilihan umum serentak dengan ketentuan presidensial threshold memiliki legalitas atas dasar putusan Mahkamah Konstitusi. Implikasi aturan presidential threshold pada pemilu serentak 2019 didasari atas: pertama, presidential threshold secara konstitusionalitas masih berlaku untuk pemilu serentak 2019. Kedua, presidential threshold dilandasi oleh konstitusionalitas putusan Mahkamah Konstitusi atas legalitas Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Dalam putusan Mahkamah Konstitusi Nomor 53/PUU-XV/2017, Mahkamah Konstitusi menegaskan bahwa meski pemilu digelar secara serentak, keberlakuan presidential threshold masih relevan untuk digunakan.